(3GdCjGe GdCNjQI ef MjGI QShd Gddg Udi Gddg Ydjg hSde (B:s (3OQGSI dCge GdbVGjG GdeQJHWI HeQV GdfHj Udi Gddg Ydjg hSde hhaGJg (B/s - (3GdMeO, YGOd MSf jhSas; (3GdSdej, eMeO Hf UGed Hf Uhjed,s 1369 (3gLQjG(B-s ((3GdefGeI (B:s (3ecJHI hOGQ Gdjbjf,s, 2004)
(3jJfGhd gPG GdcJGH HGdJaUjd GdCjGe GdCNjQI ef MjGI GdQShd Udi Gddg Ydjg hBdg hSde hjHjf CHQR GdLhGfH GdgGeI GdJj ChUi HgG HYO haGJg(B.s
Keywords: (3eMeO (B((3Udi Gddg Ydjg hSde(B)(3,s -- 53 (3bHd GdgLQI(B-11 (3gLQjG(B.s; (3GdSjQI GdfHhjIs